2012
DOI: 10.1021/ml300288d
|View full text |Cite
|
Sign up to set email alerts
|

d-Amino Acid-Based Protein Arginine Deiminase Inhibitors: Synthesis, Pharmacokinetics, and in Cellulo Efficacy

Abstract: The protein arginine deiminases (PADs) are known to play a crucial role in the onset and progression of multiple inflammatory diseases, including rheumatoid arthritis, inflammatory bowel disease, and cancer. However, it is not known how each of the five PAD isozymes contributes to disease pathogenesis. As such, potent, selective, and bioavailable PAD inhibitors will be useful chemical probes to elucidate the specific roles of each isozyme. Since D-amino amino acids often possess enhanced in cellulo stability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 27 publications
1
46
0
Order By: Relevance
“…Previous studies have shown that inhibiting PADI activity in the mouse early embryos using 250 μM of the pan-PADI inhibitor, Cl-amidine, blocked early cleavage divisions in vitro, with embryos mainly arrested at the 2- and 4-cell stages21. We found that specifically inhibiting PADI1 activity with 100 μM of the PADI1-specific inhibitor D-Cl-amidine, a next generation Cl-amidine analogue22, did not affect oocyte maturation or pronuclear formation. Zygotes cultured under 100 μM D-Cl-amidine successfully proceeded through the first two cleavages and reached the 4-cell stage, at the same time as that in the phosphate-buffered saline (PBS) control group (Fig.…”
Section: Resultsmentioning
confidence: 51%
“…Previous studies have shown that inhibiting PADI activity in the mouse early embryos using 250 μM of the pan-PADI inhibitor, Cl-amidine, blocked early cleavage divisions in vitro, with embryos mainly arrested at the 2- and 4-cell stages21. We found that specifically inhibiting PADI1 activity with 100 μM of the PADI1-specific inhibitor D-Cl-amidine, a next generation Cl-amidine analogue22, did not affect oocyte maturation or pronuclear formation. Zygotes cultured under 100 μM D-Cl-amidine successfully proceeded through the first two cleavages and reached the 4-cell stage, at the same time as that in the phosphate-buffered saline (PBS) control group (Fig.…”
Section: Resultsmentioning
confidence: 51%
“…2G (bottom row). To help answer whether PAD1 enzymatic activity contributes to these biological phenotypes, we treated MDA-MB-231 cells with a newly developed arginine-based PAD1 inhibitor, D-Cl-amidine, which has been shown to effectively inhibit PAD1 activity in breast cancer cell lines [41]. Results showed that inhibiting PAD1 activity significantly inhibited cell proliferation (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, novel anti-TNBC agents targeting tumor cell migration and invasion are urgently needed [54]. Our finding that PAD1 specific inhibitor, D-Cl-amidine, is successful in suppressing tumor growth in a xenograft mouse model of TNBC together with our previous in vitro study showing that D-Cl-amidine also effectively inhibits cell viability [41], suggests that inhibiting PAD1 could potentially be utilized as a good strategy to treat metastatic breast cancer. Further studies aimed at developing PAD1-selective inhibitors and then evaluating the pharmacokinetics, biodistribution, and anti-tumor effects of these compounds in preclinical models of cancer will represent important next steps towards advancing our overall goals.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitor potency and selectivity were evaluated for PADs 1–4 24 25. Cell growth inhibition was evaluated by the XTT assay.…”
Section: Methodsmentioning
confidence: 99%